2021
DOI: 10.1080/21655979.2021.1888596
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of long noncoding RNA MNX1-AS1 in human cancers: a meta-analysis of cohort studies and bioinformatics analysis based on TCGA datasets

Abstract: MNX1-AS1 expression has been proposed to be abnormally upregulated in multiple human malignancies and be linked with the survival outcome of patients. However, relevant conclusions were yielded based on the limited samples. Therefore, we herein implemented a meta-analysis of the published cohort studies to further decipher the relationship of MNX1-AS1 level to prognosis and clinicopathological features in various cancers. Additionally, using The Cancer Genome Atlas (TCGA) datasets we carried out a bioinformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(71 reference statements)
0
7
0
Order By: Relevance
“… 30 High MNX1-AS1 levels are correlated with poor survival outcome and aggressive clinicopathological characteristics in various cancers, suggesting that MNX1-AS1 may be applied as a prognostic marker and even a therapeutic target. 31 In the miRNA–lncRNA pair centered regulatory network consisting of competing triplets in ovarian cancer, AC099850.4 is one of the top five lncRNAs with the most connections. 32 Studies have shown that LINC02154 is significantly upregulated in renal cell carcinoma, and its high expression is one of the risk factors for poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 30 High MNX1-AS1 levels are correlated with poor survival outcome and aggressive clinicopathological characteristics in various cancers, suggesting that MNX1-AS1 may be applied as a prognostic marker and even a therapeutic target. 31 In the miRNA–lncRNA pair centered regulatory network consisting of competing triplets in ovarian cancer, AC099850.4 is one of the top five lncRNAs with the most connections. 32 Studies have shown that LINC02154 is significantly upregulated in renal cell carcinoma, and its high expression is one of the risk factors for poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…AL355102.4 was downregulated in clear cell renal cell carcinoma samples and indicated good prognosis when lowly expressed, which revealed that AL355102.4 tended to be risk factors with higher gene expression [18]. High MNX1-AS1 level correlated with poor survival outcome and aggressive clinicopathological characteristics in various cancers, suggesting that MNX1-AS1 may be applied as a prognostic marker and even a therapeutic target [19]. In the miRNA-lncRNA pair centered regulatory network consisted of competing triplets in ovarian cancer, AC099850.4 is one of the top ve lncRNAs with most connections [20].…”
Section: Discussionmentioning
confidence: 99%
“…We performed Gene Expression Profiling Interactive Analysis (GEPIA) based on TCGA dataset to further assess the prognostic value of securin expression in patients with solid cancers. [ 33 ] In this analysis, the Kaplan–Meier method and log-rank test were used to compare survival outcomes between patients with high securin expression and those with low expression, and HRs with 95% CIs and P values were presented using the Kaplan–Meier method curve, as previously described. [ 34 ]…”
Section: Methodsmentioning
confidence: 99%